Correlation of C-Reactive Protein and COPD Severity - Nena Milačić; Bojan Milačić; Maja Milojković; Srdjan Ljubisavljević; Sanja Vodopić; Mirha Hasanbegović; Marija Đurovic (Acta Clinica Croatica, 2016)
Chronic obstructive pulmonary disease (COPD) is a progressive pulmonary disease characterized by systemic inflammation. The aim of this study was to correlate the parameters of systemic inflammation, C-reactive protein (CPR) and total leukocyte count, with clinical indicators of the disease. Our study included 157 COPD patients, both outpatients and those hospitalized at the Knez Selo Department of Pulmonology of the Niš Clinical Centre during a six-month period, while in the phase of disease exacerbation. The symptoms of COPD in each patient were estimated by the COPD Assessment Test (CAT) and modified Medical Research Council (mMRC) dyspnea scale. The parameters of pulmonary function (FEV1 and FVC), acid-base status, body mass index, history of exacerbation and comorbidities were also evaluated. The level of CRP, but not leukocytes, showed significant correlation with the severity of clinical presentation according to GOLD classification. The higher the CRP concentration, the higher was the disease severity determined according to GOLD classification (p<0.001). There was no statistically significant difference in CRP level and leukocyte count according to comorbidities (p=0.29). The level of CRP was higher in patients with a high CAT score and mMRC scale (p<0.001). The same trend was observed for leukocyte count when compared with CAT results, but not when correlated to mMRC scale. The level of CRP during COPD exacerbation can be an independent predictor of the disease severity and paraclinical findings.